The mediating effect of reading IIUM today on the relationships among awareness, perception, and attitude with satisfaction - A.Manaf, Aini Maznina; Wok, Saodah (School of Media and Communication Studies (MENTION), UKM, 2017)
IIUMToday is the official campus newspaper for the International Islamic University Malaysia (IIUM), operated by students under the jurisdiction of the Department of Communication, established on 1 May 2014. To test the level of satisfaction in reading it, the objectives of the study are: (1) to determine the levels for reasons of visiting the IIUMToday website, awareness of, perception on, attitude toward, reading habit and satisfaction with IIUMToday among students in IIUM; (2) to test the relationships among the selected variables; and (3) to determine the mediating effect of the reading habit of IIUMToday among students on their level of satisfaction. The study uses the quantitative research design, employing the survey method with questionnaire as the research instrument for data collection. A total of 104 respondents were found to be readers of IIUMToday. Results show that there are moderate levels of awareness, perception, attitude, reading habit and satisfaction with IIUMToday. The relationship among the variables concerned are significantly positive. In addition, reading habit partially mediates the relationship between the predictors and the criterion.